Selective Determination of Vanadium(V) Using its Catalytic Effect on the Bromate Oxidation of Nuclear Fast Red - Pourreza, N.; Zavvar Mousavi, H. (Asian Journal of Chemistry, 2010)
A highly selective and sensitive catalytic method is described for the determination of trace amount of vanadium(V) based on its catalytic effect on the oxidation of nuclear fast red with bromate. The reaction was followed spectrophotometrically by measuring the change in absorbance of nuclear fast red at 517 nm. 4 min after the initiation of the reaction. In this study experimental parameters were optimized and the effect of other cations and anions on the determination of vanadium(V) was examined. The calibration graph was linear in the range of 5-100 ng ml-1 of vanadiurn(V) and 3Sb detection limit was 3.4 ng rnL -1. The method was successfully applied to the determination of vanadiurn(V) in water and steel samples.